Software Cost Estimation: A Pedagogical Proposal to Teach COCOMO - Garita-González, Gabriela (2018)
The computer science curriculum and other related academic programs show a relevant gap on software cost estimation. Usually, curriculum models related to software development recommend the inclusion of software estimation topics without specifying any particular estimation model. In addition, software estimation models are difficult to understand and the existing examples are often vague, and this without considering actual contexts. In this paper we present a pedagogical proposal to teach COCOMO in its basic and intermediate modalities, oriented to the magnitude of the final product. The model includes six sections required for a proper pedagogical approach. First, the theoretical background is explained in a very simple way. Then, there is a presentation of an actual case study, several examples, a pedagogical approach, and the respective analysis. This work is important because it is now possible to teach the software cost estimation topic by using a practical model contextualized in an actual case.